Gender differences in academic performance of entrepreneurial course - Zainal Abedin, Nur Fadhlina; Pardi, Faridah; Idris, Asma’ Rashidah (Faculty of Administrative Science and Policy Studies, 2023)
In recent years, entrepreneurial learning has become compulsory in Malaysia's public higher learning institutions. Hence, a continuous monitoring system to ensure its academic effectiveness is crucial. Among the valuable methods to examine this will be identifying gender disparity in academic performance. This study analyses the academic performance differences between male and female students taking the ENT300 (Fundamentals of Entrepreneurship) course in UiTM Negeri Sembilan. A total respondent of 119 students taking ENT300 were used as a sample for the empirical analysis of academic performance. The results exhibited gender disparity in academic performance, where the female students outperformed the male students significantly. Given the nature of the course, which is generally non-technical, the outcome is somehow within our expectations. By incorporating interactive methods in the teaching and learning process, we perceive that male students’ interest in entrepreneurial studies may be enhanced, and their academic performance will eventually improve.